Analisis Komparatif Kebijakan dan Strategi Penanggulangan Resistensi Antimikroba (AMR): Studi Kasus Negara Maju dan Berkembang - Fitri, Maghiroti; Farezni, Rian Hagi; Wiguna, Dwiky Setia; Jelli; Fortuna, Yuna (Pharmaceutical Journal, 2025)
In many developing countries, antimicrobial resistance (AMR) is clearly not just a medical issue; it is a complex issue that intersects social, cultural, and economic factors. Practices in the field show that doctors often face pressure to prescribe antibiotics based solely on assumptions, because the availability of adequate diagnostic tools is very limited. On the other hand, patients often come with requests for antibiotics for minor complaints, assuming that it is the most effective and quickest solution. Another phenomenon that is no less concerning is the free circulation of antibiotics in the market, even without a prescription. Regulations do exist, but without consistent law enforcement, these policies often only become formalities on paper and have no real impact. In addition, the use of antibiotics in the agricultural and livestock sectors also exacerbates the cycle of resistance at the ecosystem level. Therefore, efforts to combat AMR in developing countries cannot simply adopt models from developed countries. Every intervention must consider local conditions, including lifestyles, norms, and specific challenges of local communities. Without a deep understanding of the root of the problem, the interventions carried out will only be superficial and unable to significantly change the direction of the resistance rate.